IMPLICATIONS OF POLICY CHANGES IN MURABAHA FINANCING REPAYMENT PATTERNS AT PT. BANK ACEH SHARI'AH - Uswatun Hasanah; Yusriaina Yusuf (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2020)
This paper aims to find out how the repayment mechanism of murabahah financing in the forward period and after the policy change, and to find out if there is a risk caused by a decrease in margins for aceh shari'ah banks on previous financing and how Islamic law views on policy changes made by banks and customers who make changes to repayment patterns. From the results of further analysis, it shows that there are differences in the repayment mechanism of advanced period murabahah financing before and after the policy change Before the policy change, the advanced period repayment pattern used is that the bank only requires the customer to pay the remaining principal instalments plus administrative costs, while after the policy change, the advanced period repayment pattern used is that the bank will give a discount or discount to the customer. as well as according to the views of Islamic law on policy changes made by banks and customers who make changes to repayment patterns.